2016
DOI: 10.1002/nau.22981
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infections, urologic surgery, and renal dysfunction in a contemporary cohort of traumatic spinal cord injured patients

Abstract: Urologic disease is still an important source of morbidity for contemporary TSCI patients, and is more common compared to the general population. Neurourol. Urodynam. 36:640-647, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
0
27
0
3
Order By: Relevance
“…There are potentially serious consequences of inadequately treated neurogenic bladder parameters; one study found that almost 20% of SCI patients required surgical invention for adverse urodynamic parameters over a 5‐year period . In some cases, bladder dysfunction can cause renal dysfunction (estimated at 5% after SCI, and uncommon among MS patients) . Our objective was to conduct a pilot prospective, randomized, double‐blind clinical trial to assess the urodynamic efficacy of mirabegron among patients with NLUTD due to SCI or MS.…”
Section: Introductionmentioning
confidence: 99%
“…There are potentially serious consequences of inadequately treated neurogenic bladder parameters; one study found that almost 20% of SCI patients required surgical invention for adverse urodynamic parameters over a 5‐year period . In some cases, bladder dysfunction can cause renal dysfunction (estimated at 5% after SCI, and uncommon among MS patients) . Our objective was to conduct a pilot prospective, randomized, double‐blind clinical trial to assess the urodynamic efficacy of mirabegron among patients with NLUTD due to SCI or MS.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits and risks theme consists of the person's impressions of the impact bladder management techniques would have on day to day functioning, and their emotional response to specific medical risks that are alleviated or introduced with various methods of bladder management. It is interesting that renal disease is perceived as a key influencer of bladder management selection despite its rarity in the contemporary neurogenic population; other more common and troublesome complications such as urinary infections played a more variable role in the decision making . The meaning of control and confidence varied across participants; for some it was maximized with an indwelling catheter which required little need for active management, and for others it was addressed by using CIC to independently empty their bladder .…”
Section: Resultsmentioning
confidence: 99%
“…The exact risk of urosepsis if effective treatment is delayed is unknown among patients with NLUTD; in a clinical trial of antibiotics versus placebo in the general population presenting with uncomplicated urinary infections, urosepsis was not reported, and pyelonephritis was rare . However due to the higher risk of serious UTIs and urosepsis among some groups with NLUDT, these results cannot be generalized to NLUDT …”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that UTIs are common among patients with NLUTD, occurring in over 1/3 of patients in the first year after diagnosis . In spinal cord injured (SCI) patients, patients are over 10 times more likely to require a hospital admission or emergency room visit for UTI than the general population . In other NLUTD populations, such as multiple sclerosis, UTIs are similarly common .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation